Dysfunctional lens syndrome: a prospective review - Haddad,Jorge Selem (2021)
ABSTRACT The term dysfunctional lens syndrome has gained acceptance in the field and encompasses natural changes due to aging of crystalline lens. The evolution of diagnostic devices has been a key factor in better staging, understanding and characterizing of these degenerative changes. Even with these technological advances and the use of subjective classifications, such as the classic Lens Opacities Classification System, an objective staging of early dysfunctional lens syndrome has yet to be established. Ocular wavefront aberrometry and objective scatter index, associated with Scheimpflug backscatter densitometry, have proven instrumental in detecting early dysfunctional lens syndrome. Staging of early dysfunctional lens syndrome has been proposed in the literature, but no classification has been recognized worldwide. The purpose of this literature review is to assess the current state of dysfunctional lens syndrome from a technological perspective and propose a new staging system to assist surgeons in making surgical decisions.